2017
DOI: 10.1002/ejp.988
|View full text |Cite
|
Sign up to set email alerts
|

Unimpaired endogenous pain inhibition in the early phase of complex regional pain syndrome

Abstract: Conditioned pain modulation (CPM) is not impaired in the early phase of complex regional pain syndrome (CRPS) and neuralgia. Only in CRPS higher CPM was associated with lower cold pain thresholds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 71 publications
0
14
0
3
Order By: Relevance
“…Most notably, a recent study in patients with complex regional pain syndrome for less than 1 year demonstrated greater CPM compared with healthy controls. 48 This could be explained by neuropathic pain symptoms initially and defensively boosting or engaging CPM, momentarily increasing antinociceptive functions (eg, descending control). Greater CPM associated with neuropathic pain at Admission cannot, however, be maintained in light of persistent symptoms (ie, at Discharge), eventually leading to reductions in CPM.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, a recent study in patients with complex regional pain syndrome for less than 1 year demonstrated greater CPM compared with healthy controls. 48 This could be explained by neuropathic pain symptoms initially and defensively boosting or engaging CPM, momentarily increasing antinociceptive functions (eg, descending control). Greater CPM associated with neuropathic pain at Admission cannot, however, be maintained in light of persistent symptoms (ie, at Discharge), eventually leading to reductions in CPM.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated, unconditioned painful stimulations are commonly used to study phenomena such as temporal summation of pain (Gehling et al., ; Kumowski et al., ), and one study used repeated test‐stimuli to test for after‐effects of a single conditioning epoch (Fujii et al., ). No studies have previously evaluated the effects of repeated, individual test‐stimuli and compared them to repeated CPM‐effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies were included in the qualitative analysis based on z-scores [ 14 , 39 , 40 , 53 , 61 , 66 , 68 , 71 73 ], and the frequencies of gain and loss of sensations in CRPS were mentioned in six studies (Table 5 ) [ 14 , 15 , 44 , 53 , 65 , 69 ]. Twenty-six studies were included in the quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that investigated endogenous pain modulation could not be used in the meta-analysis because of different methodological approaches [ 45 , 53 ]. One study used repetitive electrical stimuli [ 45 ], while the other study used a restricted CPM paradigm [ 53 ].…”
Section: Resultsmentioning
confidence: 99%